Celebrating life in the face of death. Issue 2 (4th May 2017) - Mitchell, Jessica
Abstract: More than 480, 000 people die each year in England and yet many people still find it difficult to talk about dying and bereavement. Dying Matters was set up in 2009 by the National Council for Palliative Care 1 charity as a coalition of organisations that aims to help people start those conversations. In this article, Jessica Mitchell finds out more about their 2017 photography competition 'Celebrating life in the face of death'.